Cemiplimab in locally advanced or metastatic cutaneous squamous cell carcinoma: prospective real-world data from the DRUG Access ProtocolResearch in context - Karlijn Verkerk; Birgit S. Geurts; Laurien J. Zeverijn; Vincent van der Noort; Henk M.W. Verheul; John B.A.G. Haanen; Astrid A.M. van der Veldt; Ferry A.L.M. Eskens; Maureen J.B. Aarts; Carla M.L. van Herpen; Mathilde Jalving; Jourik A. Gietema; et al. (Elsevier, 2024)
Summary: Background: The DRUG Access Protocol provides patients with cancer access to registered anti-cancer drugs that are awaiting reimbursement in the Netherlands and simultaneously collects prospective real-world data (RWD). Here, we present RWD from PD-1 blocker cemiplimab in patients with locally advanced or metastatic cutaneous squamous cell carcinoma (laCSCC; mCSCC). Methods: Patients with laCSCC or mCSCC received cemiplimab 350 mg fixed dose every three weeks. Primary endpoints were objective clinical benefit rate (CBR), defined as objective response (OR) or stable disease (SD) at 16 weeks, physician-assessed CBR, defined as clinician's documentation of improved disease or SD based on evaluation of all available clinical parameters at 16 weeks, objective response rate (ORR), and safety, defined as grade ≥ 3 treatment related adverse events (TRAEs) occurring up to 30 days after last drug administration. Secondary endpoints included duration of response (DoR), progression-free survival (PFS), and overall survival (OS). Findings: Between February 2021 and December 2022, 151 patients started treatment. Objective and physician-assessed CBR were 54.3% (95% CI, 46.0-62.4) and 59.6% (95% CI, 51.3-67.5), respectively. ORR was 35.1% (95% CI, 27.5-43.3). After a median follow-up of 15.2 months, median DoR was not reached. Median PFS and OS were 12.2 (95% CI, 7.0-not reached) and 24.2 months (95% CI, 18.8-not reached), respectively. Sixty-eight TRAEs occurred in 29.8% of patients. Most commonly reported TRAE was a kidney transplant rejection (9.5%). Interpretation: Cemiplimab proved highly effective and safe in this real-world cohort of patients with laCSCC or mCSCC, confirming its therapeutic value in the treatment of advanced CSCC in daily clinical practice. Funding: The DRUG Access Protocol is supported by all participating pharmaceutical companies: Bayer, Janssen, Lilly, Merck, Novartis, Roche, and Sanofi.